Understanding the evolution of moisture during isothermal dehydration of glutinous rice through global sensitivity analysis - Jimoh, Kabiru Ayobami; Hashim, Norhashila; Shamsudin, Rosnah; Che Man, Hasfalina; Jahari, Mahirah; Putri, Renny Eka (Elsevier, 2024)
This study examined the effect of layer thickness and temperature on the evolution of moisture during the isothermal dehydration of glutinous rice. To analyse the moisture evolution, empirical models and secondary models (SM) were employed. Global sensitivity analysis (GSA) was used to estimate the importance of the experimental parameters on the developed SM. According to the dehydration curves, the increase in temperature and reduction in the layer thickness significantly shortened (P<0.05) the dehydration time of glutinous rice. The effective diffusivity, activation energy, and Gibb-free energy were 2.0×10−12m2/s to 2.53×10−11m2/s, 43.03 kJmol−1 to 51.05 kJmol−1, and 145.10 kJmol−1 to 155.85 kJmol−1respectively. The Page and Logarithmic models are suitably considered in evaluating the dehydration kinetics of the glutinous rice with a high coefficient of determination (R2) values of >0.9989. The SM aptly described moisture evolution with higher accuracy of R2=0.9843. The GSA shows that the variation in the SM output is primarily driven by the variation in the input parameters with low reliance on its interaction with other parameters, indicating that the SM can play a significant role in the optimization of the industrial dehydration process with a wide range of applications in the agricultural production system.